Penguasaan Kalimat Efektif sebagai Kunci Peningkatan Keterampilan Menulis Eksposisi - Dinari Oktaria; NFN Andayani; Kundharu Saddhono (Metalingua: Jurnal Penelitian Bahasa, 2017)
Writing is the highest form of culture to record brilliant ideas of the academics.Such writing be done in exposition texts. Mastering effective sentences as an elementof scientific language can improve the exposition writing skill. This article aims todetermine the relationship between the mastery of effective sentences and the skill ofwriting exposition texts. This research was conducted in SMA Negeri 5 Surakarta.The method used is correlational survey method. The study population was all of Xgrade students in SMAN 5 Surakarta, as many as 120 people, taken by proportionalrandom sampling. Instruments for collecting data is a test of skill to write textexposition, effective sentences mastery tests, and writing activeness questionnaires.The data were analyzed using statistical technique of regression and correlation Theresult showed that there is a positive correlation between the mastery of effectivesentences and the writing activeness along with the skill to write exposition text(ry1=0,57 at the real level of α=0,05 and N=120, rt=0,177, dan t1=7,45˃tt= 1,645).Based on the results it is concluded that both the mastery of effective sentences andthe activeness of writing give a significant contribution (34.81%) in the skills ofwriting exposition text. It shows that these two variables can be a good predictor forthe skill of writing exposition text.  AbstrakMenulis merupakan budaya peradaban tertinggi untuk mencatat gagasan cemerlangpara akademisi. Hal itu dapat dilakukan dalam kegiatan menulis eksposisi.Penguasaan kalimat efektif sebagai unsur bahasa ilmiah dapat meningkatkanketerampilan menulis eksposisi. Penelitian ini bertujuan untuk mengetahui hubunganpenguasaan kalimat efektif dengan keterampilan menulis teks eksposisi. Penelitianini dilaksanakan di SMA Negeri 5 Surakarta. Metode penelitian yang digunakanadalah survei korelasional. Populasi penelitian ini adalah seluruh siswa kelas X diSMA Negeri 5 Surakarta. Sampel berjumlah 120 orang, diambil menggunakan SimpleRandom Sampling. Instrumen pengumpulan data adalah tes menulis teks eksposisi,penguasaan kalimat efektif dan angket keaktifan menulis. Teknik analisis yangdigunakan adalah teknik statistik regresi dan korelasi. Hasil analisis menunjukkanada hubungan positif penguasaan kalimat efektif dengan keterampilan menuliseksposisi (ry1=0,57 taraf nyata α=0,05 dengan N=120, rt=0,177, dan t1=7,45˃tt=1,645). Hasil penelitian menunjukkan bahwa penguasaan kalimat efektif memberikansumbangan yang berarti (34,81%) pada keterampilan menulis teks eksposisi.